Corrosion of laser joined silicon carbide in gasification environment. (August 2015) - Schaafhausen, S.; Börner, F. D.; Chand, T.; Lippmann, W.; Hurtado, A.; Müller, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The production of synthesis gas from renewable fuels is an emerging technology. The aggressive process environment in fuel production systems poses a major challenge, potentially causing corrosion within currently used metallic heat exchangers. To improve the reliability and stability of silicon carbide heat pipes, which belong to an innovative heat exchanger design, the corrosion of involved materials due to contact with steam, ash and alkaline (earth) metals needs to be investigated. Exposures of laser joined SSiC connections with wood ash caused the formation of gas inclusions and an infiltration of the joint with alkaline (earth) metals that lead to crack formations, as revealed by energy dispersive X-ray spectroscopy analysis. It was shown that the use of silicon carbide heat pipes joined with solder materials of both the Mg–Al–Si and the Y–Al–Si systems is possible. A further result was that the gasification temperature has to be limited to < 850°C.